Study on Palladium(II) Complexes of Schiff Base - Dagaonkar, Shaila; Mehta, B.H. (Asian Journal of Chemistry, 2010)
A series of eight complexes of palladium(II) have been synthesized using Schiff bases derived from 2-hydroxy-1-naphthaldehyde and various amines. The complexes have been characterized by elemental analysis, magnetic measurements, UV/visible absorption spectral studies, infrared spectral studies, diffused reflectance spectra and conductance measurements. All the complexes were assigned square-planar configuration.